How To Use Axıograph And Normal Axıographıc Tracıngs Of Asymptomatıc Patıents - Nazan Küçükkeleş; Kerem Aras; Barış Ünlü (Galenos Yayinevi, 1996)
In order to diagnose TMJ problems, tracings of normal asymptomatic joints might be a guide for clinicians. In this study, the aim was to determine normal axiographic tracings and maximum interincisal opening values of Class 1 individuals with no joint symptomes. Left and right condylar movements of 20 individuals have been recorded with SAM axiograph. Taking the longest tracings; length of protrusionretrusion movement, length of opening-closing movement, initial inclination for opening tracing, initial inclination for protrusion tracing have been measured. Maximum interincisal opening was also measured clinically. Means and standard deviations of all these measurements were calculated.